Equilibrium and Kinetic Studies for the Removal of Zn (Ii) and Cr (Vi) Ions from Aqueous Solution Using Pineapple Peels as an Adsorbent - Olowu, Rasaq Adewale; Osundiya, Medinat Olubunmi; Oyewole, Tohib Seun; Onwordi, Chionyedua Theresa; Yussuf, Olaniyi Kamil; Osifeko, Olawale O.; Tovide, Oluwakemi O. (European Journal of Applied Sciences, 2022)
Adsorption is one of the methods extensively reported to have been successfully used for the removal of potentially toxic metals (PTMs) from wastewater. In this study, the equilibrium and kinetics studies of the application of pineapple peels as an adsorbent for the removal of Zn(II) and Cr(VI) ions from aqueous solutions was investigated in a batch process. The initial and equilibrium metal ion concentrations of the solutions were determined by Atomic Absorption Spectroscopy. The characterization of the adsorbent was done using the Scanning Electron Microscope and Fourier Transform Infrared Spectroscopy (FTIR). The FTIRspectra confirmed that there are different functional groups in adsorbents, which are able to react with metal ions in aqueous solution. Effects of initial pH, initial metal ions concentrations, shakingtime and solid/liquid ratio on metal ions biosorption were also investigated. Adsorption of metal ions were pH dependent and the results indicate that the optimum pH for the removal of Zn (II) and Cr (IV) was found to be 6.0and the maximum percentage removal of Zn (II) and Cr (IV)at this pH were 86.45% and 92.56% respectively along the whole range of initial concentrations.Three adsorption isotherm models, Langmuir, Freundlich and Temkin were used to simulate the equilibrium data. The experimental data were best fitted to the Langmuir isotherm when compared with other models with the highest R2 values of 0.937 and 0.987 for Zn(II) and Cr(VI) ions respectively. The achieved results confirmed that the adsorption of zinc and chromium were in good compliance with pseudo-first-order reaction kinetic suggesting that the adsorption is apparently physisorption and the thermodynamics analysis of the result showed that the process is spontaneous and exothermic.The pineapple peels investigated in this study showed good potential for the removal of zinc and chromium from aqueous solutions